Accelerated VB 2008 - Nash, Trey (Apress : Imprint: Apress, 2008)
Visual Basic 2008 offers powerful new features, and Accelerated VB 2008 is the fastest path to mastering them, and the rest of Visual Basic, for both experienced Visual Basic programmers moving to VB 2008 and programmers moving to Visual Basic from another object-oriented language. Many books introduce VB, but very few also explain how to use it optimally with the .NET common language runtime (CLR). This book teaches both core Visual Basic language concepts and how to wisely employ VB idioms and object-oriented design patterns to exploit the power of VB and the CLR. Accelerated VB 2008 is both a rapid tutorial and a permanent reference. You'll quickly master VB syntax while learning how the CLR simplifies many programming tasks. You'll also learn best practices that ensure your code will be efficient, reusable, and robust. Why spend months or years discovering the best ways to design and code VB when this book will show you how to do things the right way, right from the start? Comprehensively and concisely explains both Visual Basic 2005 and Visual Basic 2008 features Focuses on the language itself and on how to use Visual Basic 2008 proficiently for all .NET application development Concentrates on how VB features work and how to best use them for robust, high-performance code.